2017
DOI: 10.1002/ecy.1686
|View full text |Cite
|
Sign up to set email alerts
|

Local epiphyte establishment and future metapopulation dynamics in landscapes with different spatiotemporal properties

Abstract: Abstract. Understanding the relative importance of different ecological processes on the metapopulation dynamics of species is the basis for accurately forecasting metapopulation size in fragmented landscapes. Successful local colonization depends on both species dispersal range and how local habitat conditions affect establishment success. Moreover, there is limited understanding of the effects of different spatiotemporal landscape properties on future meta population size. We investigate which factors drive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 70 publications
0
45
0
Order By: Relevance
“…This may increase their metapopulation viability and also occupancy inside protected areas; but is something that remains to be studied. Recent experimental and empirical data have shown that the future metapopulation size of the lichen Lobaria pulmonaria is foremost set by the number of host trees located in shady uncut forest conditions, not isolated from occupied trees, and by the rotation length of these host trees (Belinchón et al., ). Increased rotation times of existing and restored stands above a mean clear‐cut age of 120 years will likely also aid the implementation of national targets to increase the area cover of old forests (>120 years) in Sweden, although not by the target year 2020 (http://www.miljomal.se).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may increase their metapopulation viability and also occupancy inside protected areas; but is something that remains to be studied. Recent experimental and empirical data have shown that the future metapopulation size of the lichen Lobaria pulmonaria is foremost set by the number of host trees located in shady uncut forest conditions, not isolated from occupied trees, and by the rotation length of these host trees (Belinchón et al., ). Increased rotation times of existing and restored stands above a mean clear‐cut age of 120 years will likely also aid the implementation of national targets to increase the area cover of old forests (>120 years) in Sweden, although not by the target year 2020 (http://www.miljomal.se).…”
Section: Discussionmentioning
confidence: 99%
“…Stochastic extinction rates were assumed to be negligible (zero) from uncut occupied beech stands (e.g. Belinchón et al., ; Johansson et al., ; Snäll et al., ). Species‐specific connectivity measures to every suitable beech stand that could represent a potential dispersal source (based on species‐specific minimum suitable stand age, see below) were calculated and ranked.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…pulmonaria in the first survey, but colonized in the second survey, as offspring. However, it is also well known that a proportion of occupied trees are erroneously recorded as unoccupied, 4.4% in this study system (Belinchón et al ., ). In analyses II and III, we accounted for imperfect detection and classified some of these individuals as potential parents instead of offspring.…”
Section: Methodsmentioning
confidence: 97%